2020
DOI: 10.3904/kjim.2020.204
|View full text |Cite
|
Sign up to set email alerts
|

Systemic treatment for advanced urothelial cancer: an update on recent clinical trials and current treatment options

Abstract: After cisplatin-based chemotherapy became the standard treatment for metastatic urothelial cancer (mUC), very little progress has been made in the treatment landscape of this condition until recently. With increased knowledge about the molecular biology of mUC and advances in the field of cancer immunobiology, there has been an explosion in the number of clinical trials for mUC, and systemic treatment of mUC is rapidly changing. Despite the availability of several novel therapeutic agents, cisplatin-based cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 140 publications
(193 reference statements)
0
8
0
Order By: Relevance
“…Treatment guidelines for la/mUC have been frequently updated 41 ; a recent study reported that providers followed current guidelines for decision-making in the la/mUC setting. 15 In the present study, approximately two-thirds of physicians identified institutional guidelines—especially the NCCN guidelines, which are considered the most up to date by US providers—as an important factor informing 1L treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment guidelines for la/mUC have been frequently updated 41 ; a recent study reported that providers followed current guidelines for decision-making in the la/mUC setting. 15 In the present study, approximately two-thirds of physicians identified institutional guidelines—especially the NCCN guidelines, which are considered the most up to date by US providers—as an important factor informing 1L treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Although preoperative radiotherapy, as a single modality, can eradicate disease in a small proportion of patients undergoing cystectomy, it seems to improve local control rather than survival when compared with RC alone (93). However, radiation can synergize with immunotherapy to improve clinical outcomes by causing immunogenic cell death and increasing expression of immune markers (94). Following this hypothesis, several trials, such as RADIANT (durvalumab + radiotherapy) (NCT04543110) and RACE IT (nivolumab + radiotherapy) (NCT03529890) prior to cystectomy in MIBC, are still active.…”
Section: Radiotherapy In Mibcmentioning
confidence: 99%
“…Currently, there are no studies of neoadjuvant FGFR-targeted agents with immunotherapy combination in muscle-invasive disease. There are some concerns about FGFR-targeted therapy being a proper partner of immunotherapy, as FGFR pathway activation is associated with non-T-cell-inflamed tumors in MIBC [72]. In the perioperative setting, only infigratinib (FGFR1-3-selective tyrosine kinase inhibitor) monotherapy is currently being investigated as neoadjuvant (NCT0422804) and adjuvant (NCT04197986) treatment for locally advanced UC.…”
Section: Combination Of Immunotherapy and Other Emerging Agents Or Radiotherapymentioning
confidence: 99%